Microalgae oil and vitamin E: from nanostructuring to safety profile - da Fonseca, Elisandra da Silva Pena; de Sousa Filho, Walter Paixão; Vaucher, Rodrigo de Almeida; de Souza, Diego; Sagrillo, Michele Rorato; Fernandes, Liana da Silva (Disciplinarum Scientia | Naturais e Tecnológicas, 2022)
In the last few years, nanotechnology seeks to expand its nanocarrier systems, to increasingly ensure that the incorporated assets maintain their properties and benefits with greater efficiency and safety. Thus, nanoencapsulation has been widely used, mainly in the cosmetic industry, which aims to combine new technologies in its products that guarantee good efficacy of the active principles used in conjunction with renewable and sustainable natural bioactive. In this context, the objective of this study was to nanoencapsulate the oil extracted from the microalgae Chlorella homosphaera with the addition of the vitamin E, to guarantee the properties and stability of this oil and the vitamin, facing encapsulation. Then, evaluate the biocompatibility of the nanocapsules for a possible topical use formulation. Nanocapsules containing microalgae oil and vitamin E were produced by the nanoprecipitation method and then physically chemically characterized, after cytogenotoxicity and hemocompatibility tests with the nanoformulations were performed to assess the safety profile of the formulations. The nanocapsules showed satisfactory results, such as average particle diameter, polydispersion index, zeta potential, and pH with values within the expected limits for the formulation produced and did not show cytotoxicity in the tests performed. Concluding that nanoencapsulation is a possible alternative for using oil from the microalgal origin with vitamin E for cosmetic formulations and topical use.